Refinement of the crystal structure of ushkovite from Nevados de Palermo, República Argentina - Galliski, Miguel Angel (2002)
The crystal structure of ushkovite, triclinic, a 5.3468(4), b 10.592(1), c 7.2251(7) Å, α 108.278(7), β 111.739(7), γ 71.626(7)°, V 351.55(6) Å3, Z = 2, space group P1, has been refined to an R index of 2.3% for 1781 observed reflections measured with MoKα X-radiation. The crystal used to collect the X-ray-diffraction data was subsequently analyzed with an electron microprobe, to give the formula (Mg0.97 Mn2+ 0.01) (H2O)4 [(Fe3+ 1.99 Al0.03) (PO4) (OH) (H2O)2]2 (H2O)2, with the (OH) and (H2O) groups assigned from bond-valence analysis of the refined structure. Ushkovite is isostructural with laueite. Chains of corner-sharing {Fe3+ O2 (OH)2 (H2O)2} octahedra extend along the c axis and are decorated by (PO4) tetrahedra to form [Fe3+ 2 O4 (PO4)2 (OH)2 (H2O)2] chains. These chains link via sharing between octahedron and tetrahedron corners to form slabs of composition [Fe3+ 2 (PO4)2 (OH)2 (H2O)2] that are linked by {Mg O2 (H2O)4} octahedra.